Verbal Markers of the Concept of Peace: Psycholinguistic and Lexical Analyses - Melnyk, Iryna; Holoiukh, Larysa; Kalishchuk, Diana; Levchuk, Iryna (Lesya Ukrainka Volyn National University, 2020)
The paper is an attempt to uncover the associative semantics of the concept of ‘Peace’ as reflected in the Ukrainian national linguistic world image. The goal of the article is to carry out a psycholinguistic analysis of the concept’s verbal markers and to compare its associative and lexical meanings at the current stage of the Ukrainian language development. Free word association test involved 148 first- and second-year students of Lesya Ukrainka Volyn National University (Ukraine), Faculty of Philology and Journalism, Ukrainian native speakers aged 18-20. It has been proved that responses related to common lexical meanings of the word-stimulus ‘Peace’ recorded in modern explanatory dictionaries are predominant. 105 words-responses have become the object of the analysis – 329 word-tokens in total, out of which 44 words have been used two times or more (from 2 to 59 times –268 word-tokens in total), 61 words have been used one time only. The received responses have been differentiated according to semantic and grammatical criteria. Traditional responses which coincide with the common lexical meaning, as well as new original responses which reflect the respondents’ individual experience and are non-typical (not recorded in the dictionaries), were received. The semantic principle of the concept of ‘Peace’ words-markers’ systematization was used as the basis of forming 11 lexical semantic groups. Among the most numerous are the names related to the state of environment, people’s inner world, their physical, emotional and mental state, moral and aesthetic properties (47.1%); names that verbalize relations between people, nations, states (31.9%). The groups of semantically distant responses are mainly represented by the names of concrete names, less frequently – by the names of abstract concepts and integral syntactic structures, which have no relation to any of the lexical meanings recorded in lexicographic sources. Their semantic ties can be traced at the unconscious level which reflects the psycholinguistic meaning of this word. The conducted word association test enabled defining the extension of the concept’s psycholinguistic meaning and thus to record new fragments of the Ukrainian linguistic world image caused by historical, political, and national mental processes.
Keywords: concept of Peace; free word association test; psycholinguistic analysis; lexical analysis